Analysis of the Eleventh Grade “APHP” Students’ Learning Style to Their Reading Competence at SMK Negeri 6 Kendal - Azhura, Dea Rahma; Lestari, Siti; Wahyuni, Sri (English Education and Literature Journal (E-Jou), 2025)
This study examines the learning styles of eleventh-grade APHP students at SMK N 6 Kendal and their impact on reading competence. The research seeks to address the following questions: What are the dominant learning styles among the students, and how do these styles influence their reading comprehension? Using a descriptive qualitative method, data were collected through questionnaires, interviews, and reading tests involving 18 students from class B. The findings reveal that visual learning styles are the most dominant, with students demonstrating a strong preference for visual aids such as diagrams, videos, and PowerPoint presentations to enhance comprehension. Auditory learners, the second largest group, benefit from verbal explanations and group discussions, while a smaller number of kinesthetic learners excel in activity-based learning, such as practice and simulations. The study highlights the significant impact of aligning teaching methods with students’ learning styles to improve engagement and academic performance, emphasizing the need for varied and inclusive teaching strategies to accommodate diverse preferences